2001
DOI: 10.1007/bf02375470
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic demixing in yttria-doped zirconia part II - theoretical analysis

Abstract: Abstract. This paper presents a formal analysis of the transport processes in yttria-doped zirconia under a temperature gradient. Due to the simultaneous diffusion and drift of the species when the material is exposed to a thermodynamical potential gradient, a kinetic demixing process appears on the cationic sublattice if the diffusion coefficients of the cations are different. Experimental results obtained with yttria-doped zirconia are discussed on the basis of this analysis. They confirm that kinetic demixi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Furthermore, we have shown that the near surface composition depends on the cooling rate, indicating that segregation processes occur during cooling. In part II [27], wc have analyzed these cation redistributions in order to be able to minimize such effects in materials in which the prevailing defects are present on the anionic sublattice.…”
Section: Influence Of the Cooling Rate On ~78hmentioning
confidence: 99%
“…Furthermore, we have shown that the near surface composition depends on the cooling rate, indicating that segregation processes occur during cooling. In part II [27], wc have analyzed these cation redistributions in order to be able to minimize such effects in materials in which the prevailing defects are present on the anionic sublattice.…”
Section: Influence Of the Cooling Rate On ~78hmentioning
confidence: 99%
“…Although, cation diffusivities are normally several orders of magnitude lower than that of oxygen ions [21], at sufficiently long times, high temperatures [22], and electric fields [23][24][25], substantial cation migration may still occur. Note that the migration of the different cations are not identical; certain elements migrate faster, others slower [26].…”
Section: Discussionmentioning
confidence: 99%